Menggugah Literasi Dari Tepian Kali: Pelatihan Literasi Saung Baca “Book Island” - Dwi Ario Fajar; Muhamad Haryanto; Catur Ragil Sutrisno (Patria : Jurnal Pengabdian Kepada Masyarakat, 2020)
The community service entitled “Waking Up The Literacy From Riverside: The Training Of Literacy In “Book Island” Book Center Community”. This activity aims to improve the interest of community in Kebagusan village, Ampelgading, Pemalang in gaining and educating people suround. It also gives the training of literacy training that include educating, teaching and learning of literacy and critical literacy which help the “Book Island” Book center community to manage their organization properly. This community service gives many advantages to their community. It can be the center of literacy in the community.